Preparation for Forgiveness in Homilies - Szewczyk, Leszek (Paedagogia Christiana, 2016)
One of the basic criteria of authenticity of being a Christian is ability to forgive. One constantly needs to be brought up to this attitude. One of the missions of the Church is to bring up her members. The real upbringing should comprise a full formation of a person and relate to the ultimate aim of his/her life as well as a common good of a community. The basic educational tasks of the Church are related to accomplishment of its redemptive functions: preaching the word of God, worshipping God and pursuing love of neighbours based on healthy love of oneself. One of the most important educational means, especially with respect to religious upbringing, possessed by the Church, is homiletic preaching. Among many issues, a homily takes up a problem of forgiveness. The aim of this paper is to present a special role of a homily in preparing for forgiveness. Consecutive points present the issues of a homilist as a pedagogue, a pedagogic role of a homily and the central issue – a homily of forgiveness. The final part of the paper presents suggestions of the newly published Homiletic Directory concerning the issue of preaching on forgiveness. A homily, with its sources in the Bible and the liturgy, being an integral part of the Eucharist, helps to communicate with another person and encourages its listeners to authenticate their faith by the attitude of forgiveness.